Effects of Variety and Fertilizers on Number of Grains/Cob of Maize in Asaba Area of Delta State - E. C, Enujeke (Asian Journal of Agriculture and Rural Development, 2013)
This study carried out in the Teaching and Research Farm of Delta state University, Asaba Campus from March 2008 to June, 2010 to evaluate the effects of variety, organic manure and inorganic fertilizer on number of grain/cob of maize. The experiment was carried out in a Randomized Complete Block Design (RCBD) replicated three times in a factorial layout. Four different rates of poultry manure, cattle dung and NPK 20:10:10 fertilizer were applied to three different maize varieties sown at 75cm x 15 cm and evaluated for number of grains/cob. The result obtained indicated that hybrid variety, 9022-13, which had 5090, was superior. Also, plants that received inorganic fertilizer were outstanding in number of grains/cob with values of 441.5 in 2008 and 506.0 in 2009 followed by the plants received poultry manure (444.0 in 2008 and 468.0 in 2009). Based on the rates of application of manure/inorganic fertilizer, plants that received 450kgha-1 of NPK 20:10:10 fertilizer were outstanding in numbers of grains/cob of maize with values of 532.8 in 2008 and 570.8 in 2009. The results of interaction showed that variety, manure type and rates of application were significantly (p<0.05) different. Based on the findings of this study, it is recommended that (i) Hybrid variety 9022-13 should be grown in Asaba area. (ii) NPK 20: 10:10 mineral fertilizers should be applied at the rate of 450kgha-1 to enhance maize yield.